Students’ Anxiety in Learning English (A Case Study in SMA Negeri 1 Lawa ) - Risna Nur Hasanah; La Ode Sidu Marafad; Kammaluddin Kammaluddin (Halu Oleo University, 2019)
The research was aimed to 1) examine what factors are more probable to cause anxiety as perceived by the student in SMA Negeri 1 Lawa. 2) find out the students’ strategy to cope with their anxiety in learning English. The research design was a qualitative method. The researcher used purposive sampling to determine the subjects of this study. The subjects in this study were 12 students in grade XII MIA 1 at SMA N 1 LAWA. The techniques of data collection were interview and observation. The researcher used the technique of data analysis and validity data such as data reduction, data display, and conclusion drawing and verification. The result showed that there were differences factors of anxiety in learning English, those were ridiculed by peers, teacher's personality, English is difficult, limited vocabulary, incomprehensible input, and excessive material. The researcher also found some students’ strategies to cope with their anxiety in Learning English, those were relaxation, positive thinking, preparation resignation, and peer- seeking. For suggestions, it is better if the teachers motivate students to make them more active, confident to practice, and share their anxiety experiences in learning EnglishKeywords:Anxiety;Students’ Anxiety;Factor of Anxiety; Strategy to Reduce Anxiety